Effect of intraoperative use of low-dose dexmedetomidine on the prognosis of patients undergoing breast cancer surgery - YANG Xiaoxuan; ZHU Shan; QIAN Cheng; CHU Xiaoying (Shanghai Jiaotong Daxue xuebao. Yixue ban, 2023)
Objective·To investigate the influence of intraoperative dexmedetomidine infusion on the recurrence-free survival (RFS) and overall survival (OS) rate of patients undergoing breast cancer surgery.Methods·A retrospective analysis was performed on patients who underwent breast cancer surgery at the Breast Disease Diagnosis and Treatment Center, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine from July 2013 to June 2014. Patients were divided into dexmedetomidine group and control group according to whether dexmedetomidine was injected intraoperatively at 0.7‒0.8 ìg/kg. After correcting the confounding factors between the two groups by using the propensity score matching method, the factors affecting the prognosis and survival of patients undertaking breast cancer surgery were investigated by univariate and multivariate analysis, and the Kaplan-Meier survival curve was further used to analyze the effect of intraoperative dexmedetomidine on RFS and OS after five years of breast cancer surgery.Results·There were significant differences in age, progesterone receptor (PR) positive ratio, proliferating cell nuclear antigen (Ki67) expression score, American Society of Anesthesiologists (ASA) grade, and anesthesia duration between the two groups before propensity score matching. After propensity score matching, a total of 239 pairs were successfully matched, and there was no significant difference in baseline data and perioperative data between the two groups (P>0.05). Univariate analysis showed that age (P=0.032), postoperative radiotherapy (P=0.041), Ki67 score (P=0.021), and tumor TMN stage (P=0.029) were significantly correlated with postoperative five-year OS. The results of multivariate analysis showed that postoperative radiotherapy, Ki67 score, and tumor TMN stage were significantly correlated with postoperative five-year OS (P<0.05). Intraoperative low-dose dexmedetomidine infusion was not a risk factor for postoperative five-year OS (P>0.05). Compared with the control group, the five-year postoperative RFS and OS in dexmedetomidine group did not decrease significantly (P>0.05).Conclusion·Intraoperative use of low dosage of dexmedetomidine (0.7‒0.8 μg/kg) has no significant effect on RFS and OS in patients undergoing breast cancer surgery at five years postoperatively, providing theoretical reference for the rational selection of anesthetics for tumor patients. The effect of higher dosage of dexmedetomidine needs to be further confirmed by prospective multicenter randomized controlled studies.